Taming the Chinese Dragon: A Promising Cornerstone for Transatlantic Trade Cooperation? - Simon J. Evenett (Intereconomics, 2021)
The desire of many policymakers to tame the Chinese Dragon is apparent. But what is particularly disappointing is the little, if any, reflection on how to induce the government in Beijing to change course, whether with respect to domestic policy or foreign economic policy.
Keywords: 330; Internationale Beziehungen; Internationaler Wettbewerb; China; EU-Staaten; USA